Clinical PET Imaging of Microglial Activation: Implications for Microglial Therapeutics in Alzheimer’s Disease - Shen, Zhiwei; Bao, Xinjie; Wang, Renzhi (Frontiers in Aging Neuroscience, 2018)
In addition to extracellular β-amyloid (Aβ) plaques and intracellular neurofibrillary tangles (NFTs), neuroinflammation has been identified as a key pathological characteristic of Alzheimer’s disease (AD). As typical neuroinflammatory cells, microglia, once activated, acquire different activation phenotypes. At the early stage of AD, activated microglia are mainly dominated by the neuroprotective and anti-inflammatory M2 phenotype. Conversely, in the later stage of AD, the excessive activation of microglia is considered detrimental and pro-inflammatory, turning into the M1 phenotype. Therapeutic strategies targeting the modulation of microglia may regulate their specific phenotype. Fortunately, with the rapid development of in vivo imaging methodologies, visualization of microglial activation has been well explored. In this review, we summarize the critical role of activated microglia during the pathogenesis of AD and current studies concerning imaging of microglial activation in AD. We explore the possibilities for identifying activated microglial phenotypes with imaging techniques and highlight promising therapies that regulate the microglial phenotype in AD mice.